Urgent care axis for the older adult: where is best to target interventions?. Issue 1 (3rd September 2018) - Bunn, Jonathan Graeme; Croft, Susan Jane; O'Keeffe, Colin; Jacques, Richard M; Simpson, Rebecca M; Stone, Tony; Conroy, Simon Paul; Mason, Suzanne M
Abstract : Background: We explored the urgent care axis across EDs in Yorkshire and Humber (Y&H) for patients aged ≥75 years to identify where interventions could be targeted to prevent ED attendances and inpatient admissions. Methods: Hospital Episode Statistics (HES) data for attendances across 18 EDs in Y&H from April 2011 to March 2014 were retrospectively analysed. HES A&E and Admitted Patient Care patient records data were linked to describe the entire patient pathway. The population studied was adult patients attending type 1 EDs, comparing those ≥75 years with those under 75. Data analysed included arrival mode, presentation time, time in ED, outcome (admitted/discharged), admission length of stay, International Classification of Diseases 10th Revision (ICD-10) and cause codes related to admission. Short-stay admissions and admissions with potentially avoidable conditions (identified by ICD-10 codes and cause codes) were identified. Comparative analysis was undertaken between sites. Results: There were 3 736 541 ED attendances, of which 625 772 (16.7%) were ≥75 years. Older patients were significantly more likely to attend via ambulance than the younger cohort (OR 7.7, 95% CI 7.6 to 7.7), and had significantly longer median stays within ED (195 vs 136 min, p<0.001) and increased likelihood of admission (OR 4.5, 95% CI 4.5 to 4.6). Short-stay admissions accounted for 28.3% of older adult admissions. 37.3% of older adult admissions were with conditions that were potentially avoidable, accounting for 42.3% of short-stay admissions. There was regional variation in the proportions of older adults admitted (between 34.3% and 40.9%). Discussion: Large numbers of older adults present to EDs mainly by ambulance. Significant proportions are admitted for short periods with conditions that might potentially be managed outside of hospital. Variation across the region warrants further study.